Treasure Hunt Strategy in Teaching the Literary Elements of James Joyce’s A Portrait of the Artist as a Young Man (1916) : Project – Based Teaching Approach - Prof. Ansam Yaroub Khyoon; Prof. Mayada Zuhair Alkhafaji (Journal of College of Education, 2024)
the problem of the research lies in the lack of modern strategies for teaching English novel in Iraq thus the research aims at designing and applying a treasure hunt for teaching literary elements as well as making a project about what they have learned.